Southeast Asia tourism in inflight safety video (Faculty of Communications Science, Dr. Soetomo University, 2021)
Inflight safety video is not only seen as a medium for passenger safety in flights, but has also become a medium for each country's tourism promotion strategy. The aim of this study is to know about Southeast Asian tourism in inflight safety video. The method used in this research is content analysis of the latest Inflight safety videos via YouTube which includes Garuda Indonesia, Singapore Airlines and Philippine Airlines as Southeast Asian airlines owned by the Government of each country. The conclusion reached in this study is that the Inflight Safety Video is used by all ASEAN countries for the promotion of tourism, as well as for the equalization of new tourism destinations in each ASEAN country. In addition, efforts are also being made to increase foreign exchange income from the tourism sector, so that tourist activities are not limited to one of the tourist destinations well known to both local and foreign tourists. Keywords: Tourism, Southeast Asia, Inflight Safety Video, Content Analysis.